2017
DOI: 10.1007/s00442-017-3886-4
|View full text |Cite
|
Sign up to set email alerts
|

Habitat quality mediates personality through differences in social context

Abstract: Assessing the stability of animal personalities has become a major goal of behavioral ecologists. Most personality studies have utilized solitary individuals, but little is known on the extent that individuals retain their personality across ecologically relevant group settings. We conducted a field survey which determined that mud crabs, Panopeus herbstii, remain scattered as isolated individuals on degraded oyster reefs while high quality reefs can sustain high crab densities (>10 m). We examined the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“…An observation seen previously in this system (Toscano et al., ), but which had not been tested across different quality habitats. Although crabs transplanted to different quality reefs may have altered their behavior and consequently their predation risk/dispersal propensity, previous personality studies in this system which span different environmental contexts (e.g., predation risk and conspecific density) found that relative behavioral differences between individuals remain similar when crabs shift their behavior to match environmental circumstances (Belgrad & Griffen, ; Griffen et al., ). In fact, the behavioral changes observed in transplanted crabs suggest that these differences in community interactions may be magnified by habitat degradation and dispersal as bold individuals that migrate to high‐quality reefs should become bolder, while crabs that find themselves on degraded, low‐quality reefs should either migrate or become shyer.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An observation seen previously in this system (Toscano et al., ), but which had not been tested across different quality habitats. Although crabs transplanted to different quality reefs may have altered their behavior and consequently their predation risk/dispersal propensity, previous personality studies in this system which span different environmental contexts (e.g., predation risk and conspecific density) found that relative behavioral differences between individuals remain similar when crabs shift their behavior to match environmental circumstances (Belgrad & Griffen, ; Griffen et al., ). In fact, the behavioral changes observed in transplanted crabs suggest that these differences in community interactions may be magnified by habitat degradation and dispersal as bold individuals that migrate to high‐quality reefs should become bolder, while crabs that find themselves on degraded, low‐quality reefs should either migrate or become shyer.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work in this system has established that individual P. herbstii exhibit just such persistent personality differences. Specifically, differences in activity level and in refuge use between individuals on the same reef, reflecting personality, can last for months (Toscano et al., ) and are consistent across a range of different conditions, including predator presence/absence (Griffen et al., ), conspecific density changes (Belgrad & Griffen, ), and starvation levels (B. A. Belgrad 2015, unpublished data).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…(). We selected crabs as they were “wandering” the beach, rather than targeting aggregations, because this social context could alter crabs’ response (Belgrad & Griffen, ). For the same reason, they were tested away from other crabs (no crab was allowed within 2 meters of the focal individual).…”
Section: Methodsmentioning
confidence: 99%
“…Crabs were tested four times for startle time (the time taken for the crab to emerge from the shell after being tapped) following some of the methods provided in and Watanabe et al (2012). We selected crabs as they were "wandering" the beach, rather than targeting aggregations, because this social context could alter crabs' response (Belgrad & Griffen, 2017). For the same reason, they were tested away from other crabs (no crab was allowed within 2 meters of the focal individual).…”
Section: Behavioral Testsmentioning
confidence: 99%